Study on the lipid and flavor compounds of Hibiscus manihot L. oil induced by different pressing method - Yan, Xinlei; Yang, Nafei; Chen, Baiting; Miao, Jing; Guo, Jiaqi; Sun, Yufei; Wang, Jing; Guo, Wenhui; Zhang, Xiujuan; Yang, Feiyun; Wang, Ruigang (Frontiers in Sustainable Food Systems, 2023)
Hibiscus manihot L. seed oil is an emerging high-value edible vegetable oil that also has a variety of important health functions, and concerns about its pressing method have great significance for commercial and consumer health. This study compared triacylglycerols (TAGs), diacylglycerol (DAG), free fatty acids (FFAs), and volatile flavor compounds for discriminating cold-pressed oil from hot-pressed oil. The profiles of TAGs, DAGs, FFAs, and flavor compounds were established by a lipidomic approach and electronic-nose (E-nose). Our results demonstrated that a slight decrease in TAG content and a significant increase in FFA and DAG contents were observed after roasting. The E-nose results showed that sulfides, terpenes, methane, compounds containing oxygen and nitrogen, alcohol and aromatic compounds greatly influenced the oil flavor. The PCA results of the E-nose data indicated that flavor compounds showed great promise for distinguishing the two samples. The quality indices and the oxidative stability of oil samples were detected to identify their nutritional value and edible quality. This study revealed that roasting greatly influenced the lipid and flavor substances of the Hibiscus manihot L. seed oil. Our findings could provide useful information on the impact of the pressing method for Hibiscus manihot L. seed oil.